Impact of Public Capital Expenditure on Economic Growth in Nigeria (Lapai Journal of Economics, 2019)
This study investigates the impacts of capital expenditure on the rate of growth of the Nigerian economy during the period 1981 to 2017 using the Engel-Granger 2–step error correction technique. The study reveals that there is a negative influence of capital spending on economic growth due to shortfall between funds disbursement and utilization. It was further discovered from the study that exchange rate and inflation rates have positive and negative relationships with economic growth respectively. More so, there appears to be cointegration between the variables and an error correction of 28.5 percent was found in the event of any disturbance in the short-term equilibrium. The study suggests that proper machinery be put in place in order to checkmate the spending and implementation of projects for which government funds are intended and a favourable flexible exchange regime which will be properly tailored to the requirements of the Nigerian economy be adopted.